Determinants of Going Concern Audit Opinions: Evidence from Textile and Garment Companies Listed on the Indonesia Stock Exchange - Nikma Bilondatu; Wahyudin Hasan; Zubaidah Rahman (Vifada Management and Social Sciences, 2026)
Purpose: This study aims to examine the effects of profitability, liquidity, firm size, debt default, and firm growth on going concern audit opinions among textile and garment manufacturing companies listed on the Indonesia Stock Exchange (IDX). Research Design and Methodology: A quantitative approach was employed using multiple linear regression analysis with the assistance of Statistical Package for the Social Sciences (SPSS). The study utilized secondary data obtained from the annual financial reports of 18 textile and garment manufacturing firms listed on the IDX during the 2023–2025 period, resulting in 54 firm-year observations selected through purposive sampling. Findings and Discussion: The results indicate that profitability, firm size, and firm growth have a negative and significant effect on going concern audit opinions. In contrast, debt default has a positive and significant effect on the likelihood of receiving a going concern audit opinion, while liquidity does not significantly influence the auditor’s opinion. These findings suggest that financial performance and debt-related conditions are important considerations in auditors’ assessments of business continuity. Implications: The study provides practical insights for auditors, managers, and investors regarding the financial determinants of going concern audit opinions. Future research is encouraged to incorporate additional governance and macroeconomic variables and extend the observation period to enhance the generalizability of the findings.